Adrenal Vein Sampling in the Management of Primary Aldosteronism: The Added Value of Intraprocedural Cortisol Assessment - Manique, I (2023)
Introduction: Primary aldosteronism is the most common cause of secondary hypertension. Adrenal vein sampling is the gold standard for subtyping primary aldosteronism. However, this procedure is technically challenging and often has a low success rate. Our center is one of the very few performing this technique in our country with an increasing experience. Objective: The aim of this study was to evaluate the role of the cortisol intraprocedural assay in improving the performance of adrenal vein sampling. Design: We enrolled all of the patients with primary aldosteronism that underwent adrenal vein sampling from February 2016 to April 2023. The cortisol intraprocedural assay was introduced in October 2021. Methods: We enrolled a total of 50 adrenal vein samplings performed on 43 patients with the diagnosis of primary aldosteronism. In this sample, 19 patients and 24 patients underwent adrenal vein sampling before and after intraprocedural cortisol measurement, respectively. The procedure was repeated in seven patients (one before and six after intraprocedural cortisol measurement), given the unsuccess of the first exam. Selectivity of the adrenal vein sampling was assumed if the serum cortisol concentration from the adrenal vein was at least five times higher than that of the inferior vena cava. Lateralization was assumed if the aldosterone to cortisol ratio of one adrenal vein was at least four times the aldosterone to cortisol ratio of the contralateral side. Results: The mean age of the patients that underwent adrenal vein sampling (N = 43) was 55.2 ± 8.9 years, and 53.5% (n = 23) were female. The mean interval between the diagnosis of hypertension and the diagnosis of primary aldosteronism was 9.8 years (±9.9). At diagnosis, 62.8% of the patients (n = 27) had hypokalemia (mean value of 3 mmol/L (±0.34)), 88.4% (n = 38) had adrenal abnormalities on preprocedural CT scan, and 67.4% (n = 29) described as unilateral nodules. There were no statistically significant differences in the patients' baseline characteristics between the two groups (before and after intraprocedural cortisol measurement). Before intraprocedural cortisol measurement, adrenal vein sampling selectivity was achieved in 35% (n = 7) patients. Selectivity increased to 100% (30/30) after intraprocedural cortisol measurement (p < 0.001). With the exception of one patient who refused it, all patients with lateralized disease underwent unilateral adrenalectomy with normalization of the aldosterone to renin ratio postoperatively. Conclusions: The lack of effective alternatives in subtyping primary aldosteronism highlights the need to improve the success rate of adrenal vein sampling. In this study, intraprocedural cortisol measurement allowed a selectivity of 100%. Its addition to this procedure protocol should be considered, especially in centers with a low success rate.